(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research :This research aims to build a proposed program according to social theory to teach the curriculum and textbook subject to students of basic education faculties, and to know the importance of social theory in learning knowledge and its active role in developing students’ capabilities by building and developing knowledge of themselves, and that social theory is one of the most important theories in Modern educational trends in the teaching and learning processes and received wide attention in modern educational thought because they link the educational process to the students’ environment.To achieve the goal of the research, the researcher prepared an open questionnaire for teachers who study the subject of the curriculum and the textbook to investigate their opinions and ideas about this subject, and an open questionnaire for students of the fourth stage to know the difficulties they face in this subject, and then the researcher built a program (proposed educational content) according to social theory and presented The educational content (Student’s Guide) and the strategies in light of which the content is taught (Teacher’s Guide) on a selection of experts and arbitrators to verify its validity in teaching